Who cares for the children ? - Davis, David; Baker, Bobbie; Filmakers Library Inc.. New York (Seattle : KCTS Association, 1988)
Through the eyes of parents, providers, children and experts, Who Cares for The Children examines the current child-care crisis. It shows that child care costs are generally the second highest expense of the typical American family, just below housing. yet the wages of child care providers are so low that turnover is a staggering 40 percent a year
Music, Denney Gore ; editor, Karla Davison Steeves ; host, Rhea Pearlman
Keywords: Child care -- United States; Day care centers -- United States; Child care centers -- United States